The immune system response to the SARS-CoV-2 virus - Klenerman, Paul (Henry Stewart Talks, 2020)
Current knowledge on the immune response to SARS-COV-2, How the response to the novel virus is being studied, The possibility of future health issues in infected individuals, Future steps in the research into a COVID-19 infection